Pattern of kidney diseases in Northern India: an overview through histopathological findings in biopsy-proven cases - Sanjay Kumar; Anita Kumari; Satish C. Agrawal (SpringerOpen, 2020)
Abstract Background A kidney biopsy is being increasingly performed for the diagnosis of renal diseases. It is a reasonably safe procedure that helps not only to reach the correct diagnosis based on histopathological findings but also helps in predicting the clinical course and outcome. The pattern of kidney diseases varies not only in far apart geographical regions but also in the same country. This study was done to evaluate the demographic pattern and spectrum of kidney diseases in renal biopsy-proven cases in an admitted patient of a tertiary care hospital of northern India. Results The mean age of patients was 41.3 years ± 18.39 years, and the male-to-female ratio was 1.7:1. The most common indication for biopsy in this study was nephrotic syndrome (40.5%). The primary glomerular disease was most common, accounting for 57.5% of cases. Membranous nephropathy (MN) was the most frequently observed histopathological diagnosis not only in the primary glomerular disease category (22.9%) but of all cases (13.2%) as well. Among secondary cases, diabetic nephropathy was most frequent, constituting 43.4% cases. Interstitial and vascular diseases accounted for 18.8% and 1.8% of total cases, respectively. While minimal change disease (MCD) was the most common diagnosis in < 18-year age group, membranous nephropathy was most common above this age. Regarding the gender factor, membranoproliferative glomerulonephritis had an equal distribution among both genders, while MCD had a female preponderance. Conclusions Primary glomerular disease is the predominant kidney disease in northern India with MN being the most common histopathological diagnosis. The spectrum of kidney diseases varied with patient's age and gender.